New slot management scheme supporting ONU sleep mode - Yin-fa ZHANG; Lei JIA; Jian YANG; Tao LIU (Tongxin xuebao)
Aimed at the problem of optical network units(ONU) energy saving,a new based on the polling cycle time slot management scheme was proposed.In this scheme,polling cycle was a bandwidth allocation unit,and the transceiver time slots for each ONU were assigned at the beginning of each polling cycle,then the slot allocation information was broadcasted to each ONU through a modified GATE frame.Each ONU received the GATE frame,and extracted its own slot allocation information,and thus received or transmitted data within the allocated time slots in the polling cycle.When there was no need for receiving or transmitting data,the ONU would go into sleep mode with low energy consumption.Theoretical analysis and numerical simulation calculations show that the ONU with new time slot management scheme is only 11% of the energy consumption of the ordinary ONU,While the introduction of the downlink packet delay don’t exceed 2ms,and downlink average queue length is less than 2Mbit.